2009
DOI: 10.1007/s10620-009-0930-1
|View full text |Cite
|
Sign up to set email alerts
|

Urocortin Prevents Indomethacin-Induced Small Intestinal Lesions in Rats Through Activation of CRF2 Receptors

Abstract: These results suggest that urocortin 1 prevents indomethacin-induced small intestinal lesions, and that this action is mediated by the activation of CRFR2 and is functionally associated with the suppression of the intestinal hypermotility response caused by indomethacin. It is assumed that endogenous CRF contributes to the maintenance of the mucosal defensive ability of the small intestine against indomethacin through the activation of CRFR2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 53 publications
(94 reference statements)
1
20
0
Order By: Relevance
“…Ucn1 binds with equal affinities to both CRF 1 and CRF 2 , but binds with a ten-fold higher affinity to CRF 1 than to CRF (15). Others and we have shown that Ucn1 and CRF 2 are required for normal resolution of GI inflammatory diseases like colitis (9,13,14,16,17). The lack of CRF 2 in the GI tract leads to increased inflammation and delayed healing (9,13,18), perpetuating the insult.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Ucn1 binds with equal affinities to both CRF 1 and CRF 2 , but binds with a ten-fold higher affinity to CRF 1 than to CRF (15). Others and we have shown that Ucn1 and CRF 2 are required for normal resolution of GI inflammatory diseases like colitis (9,13,14,16,17). The lack of CRF 2 in the GI tract leads to increased inflammation and delayed healing (9,13,18), perpetuating the insult.…”
Section: Introductionmentioning
confidence: 67%
“…Others and we have shown that Ucn1 and CRF 2 are required for resolution of GI inflammatory diseases like gastritis and colitis (9,13,14,16,17,31,49). Loss of CRF 2 leads to increased inflammation, delayed healing, and exacerbates the inflammatory insult (9,18,43).…”
Section: Discussionmentioning
confidence: 87%
“…The intestinal ulcerogenic response to indomethacin was also found to be suppressed by urocortin I, a nonselective corticotropin-releasing factor receptor (CRFR) agonist, and aggravated by astressin, a nonselective CRFR antagonist [47]. Furthermore, the protective effects of urocortin I were reversed by astressin-2B (a CRFR2 antagonist), but not by NBI-27914 (a CRFR1 antagonist).…”
Section: Effects Of Various Drugs On Nsaid-induced Small Intestinal Dmentioning
confidence: 99%
“…CRF and CRF-related peptides are also involved in inflammatory responses in the intestine; however, their roles are not without controversy [ 12 - 16 ]. Kokkotou et al .…”
Section: Introuctionmentioning
confidence: 99%